2010
DOI: 10.1007/s13105-010-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Gliadins induce TNFα production through cAMP-dependent protein kinase A activation in intestinal cells (Caco-2)

Abstract: Celiac disease is an autoimmune enteropathy caused by a permanent intolerance to gliadins. In this study the effects of two gliadin-derived peptides (PA2, PQPQLPYPQPQLP and PA9, QLQPFPQPQLPY) on TNFalpha production by intestinal epithelial cells (Caco-2) and whether these effects were related to protein kinase A (PKA) and/or -C (PKC) activities have been evaluated. Caco-2 cell cultures were challenged with several sets of gliadin peptides solutions (0.25 mg/mL), with/without different activators of PKA or PKC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It has been previously reported that intestinal PKIA gene expression was increased among patients with untreated celiac disease [ 29 ]. Another study suggests a potential role of cAMP-dependent protein kinase-A activation in the TNF-alpha production by gliadin-derived peptides in intestinal epithelial cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that intestinal PKIA gene expression was increased among patients with untreated celiac disease [ 29 ]. Another study suggests a potential role of cAMP-dependent protein kinase-A activation in the TNF-alpha production by gliadin-derived peptides in intestinal epithelial cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines, overall IL-1β, TNF-α, IL-6 and IL-13, released in sites of immune processes, also activate the hypothalamus-inducing release of pituitary PRL [15]. In CD patients, the production of these inflammatory cytokines is increased by the ingestion of gliadin with food [32,33,34,35,36,37,38]. PRL increases the production of interferon-γ by lymphocytes and induces the expression of IL-2 receptors on the surface of lymphocytes [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in irritable bowel syndrome (IBS), alterations in microbial diversity [ 103 ] are seen in addition to gut-related inflammation as pivotal mediators of endotoxemia, systemic inflammation and neuroinflammation, all of which are documented as contributing factors to cognitive impairment [ 104 , 105 , 106 , 107 , 108 , 109 ]. Many of the foods that abound in Western diets are rich in substances such as gliadins (a component in gluten), which have endotoxin-like effects [ 110 ] that can elicit aberrant immune responses [ 111 , 112 ]. Other proteins such as casein and zein have also been observed to have similar effects in animal models [ 113 ].…”
Section: The Microbiota-gut-brain Axis: a Complex Communication Symentioning
confidence: 99%